2014
DOI: 10.1177/0743558414546718
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extended Family in Teen Sexual Health

Abstract: Despite increasing extended family involvement in childrearing, particularly in minority families, few studies investigate their role in talking with teens about sex or how this relates to teens’ sexual behavior. This mixed methods study assesses extended family sexuality communication through a survey of 1492 diverse middle school students and interviews with 32 students. Logistic regression shows that participants who report having had sex are more likely to report talking with extended family than those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
2
24
0
2
Order By: Relevance
“…The high number of teens who talk with extended family about sex [4,5] and the associations of this communication with teens' sexual behavior [4,46] suggest the need to understand extended family roles in sexuality communication. This study is one of the first to provide an in-depth exploration of extended family perspectives on family sexuality communication.…”
Section: Discussionmentioning
confidence: 99%
“…The high number of teens who talk with extended family about sex [4,5] and the associations of this communication with teens' sexual behavior [4,46] suggest the need to understand extended family roles in sexuality communication. This study is one of the first to provide an in-depth exploration of extended family perspectives on family sexuality communication.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent or high parent-youth communication on sex reduced the odds of having the intention to practice premarital sex in their sons. Based on this positive influence, it is important to highlight to parents the importance of discussing sexual issues with their children, as evidence has shown that parents tend to be biased; they communicated more with their daughters than sons and most communications were done by mothers (Grossman et al 2015;Gallegos et al 2007). In addition, a study in Thailand showed that mothers were more likely to talk about the issues only when they think their daughters were sexually active and the discussions were rather superficial, wherein they hardly discussed contraception, HIV/STD infection, or pregnancy (Rhucharoenpornpanich et al 2012).…”
Section: The Influence Of Parenting Behaviours and Family Interactionmentioning
confidence: 99%
“…While urban teens show high rates of extended family communication overall (Grossman et al 2014a, b), extended family communication may be particularly prevalent for teens of early parents. This study’s findings suggest that a dyadic model for sexuality communication, that is restricted to parents and teens, may not reflect the realities of many families.…”
Section: Discussionmentioning
confidence: 99%
“…Sex education programs that include family components have shown effectiveness in delaying teen sex (Grossman, Tracy, Charmaraman, Ceder, & Erkut, 2014; Tortolero et al 2010), but we know of no evaluations of programs that include extended family involvement. While programs have limited resources to reach out to extended family members, asking teens to identify which family members they trust to talk with about sex may help teens identify potential partners for assigned family activities (Grossman et al 2014a, b). Including extended family members as recognized resources for family assignments could also expand students’ participation in family activities, as teens may be reluctant to talk with parents about sex, especially when they become sexually active (Crohn 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation